Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang lake basin in Jiangxi Province, South China - An, Chang-Ting; Zhang, E; Shen, Jian-Zhong (Zootaxa, 2020)
Sarcocheilichthys vittatus, a new species of gudgeon, is described from the Gan-Jiang and Fu-He flowing into the Poyang Lake Basin in Jiangxi Province, South China. It is similar to S. parvus and S. caobangensis in having a longitudinal black band extending from the snout tip to the caudal-fin base, a character separating them from all other congeneric species, but distinct from S. parvus in having more lateral-line scales, no longitudinal yellowish stripe above the lateral black band on the flank and no barbels, and from S. caobangensis in possessing two shorter lateral lobes of the lower lip restricted only to the side of the lower jaw, no black spots along the dorsal-fin base and a stouter caudal peduncle. Its validity was also warranted by a molecular phylogenetic analysis based on the cyt b gene. Critical notes were provided on some currently recognized Chinese congeners.